The Influence of Halal Labels, Health Awareness, and Brand Image on the Purchase Decisions of Yakult Functional Beverages Among Female Boarding School Students at the Syafaatul Qur'an Dormitory - Siti Mujawarotul Maulidah; Lely Ana Ferawati Ekaningsih (Universitas Nurul Jadid, 2026)
This study is motivated by an empirical gap regarding the purchasing behavior of functional beverage products in closed religious communities such as Islamic boarding schools, where most previous studies have focused on the general urban population without considering how collective norms and religious compliance moderate the influence of halal labeling, health consciousness, and brand image. This study aims to analyze the partial and simultaneous effects of halal labeling (X₁), health awareness (X₂), and brand image (X₃) on the purchase decision (Y) of Yakult functional beverages. An associative quantitative design was chosen as it is suitable for testing predictive relationships among variables, not for establishing absolute causality. A sample of 134 female students at the Syafaatul Qur'an Dormitory, Darussalam Blokagung Islamic Boarding School, was selected using simple random sampling. Data were analyzed using multiple linear regression with IBM SPSS version 22. The findings indicate that the halal label (β=0.518; p<0.05) and brand image (β=0.538; p<0.05) have a significant partial effect on purchase decisions, with brand image being the strongest predictor. Conversely, health awareness had no significant influence (p>0.05), indicating that in an environment with collective religious norms and resource constraints, external assurances (halal certification and brand reputation) are more dominant than individual health motivations. Collectively, the three variables explain 72.5% of the variance in purchase decisions (R² = 0.725; p < 0.05). The contributions of this study include: (a) theoretically, proposing a modification of the Theory of Planned Behavior for a religious-collectivist context emphasizing the dominance of subjective religious norms; (b) practically, providing recommendations for functional beverage producers to prominently display halal certification and develop peer ambassador programs within pesantren environments, as well as for pesantren administrators to facilitate the availability of halal-certified products in cooperatives. Further research is recommended to: (1) test the same model using Structural Equation Modeling (SEM) with a sample from various Islamic boarding schools; (2) include moderating variables such as individual religiosity, monthly income, and peer influence; and (3) compare consumer behavior in Islamic boarding schools with non-boarding school educational institutions to test the generalizability of the findings.